2019
DOI: 10.1177/2515841419840249
|View full text |Cite
|
Sign up to set email alerts
|

An overview of optical coherence tomography angiography and the posterior pole

Abstract: Optical coherence tomography angiography is a relatively new, noninvasive technology that has revolutionized imaging of the retinal and choroidal microvasculature. This technology is based on the detection of movement or changes that represent moving red cells in sequential optical coherence tomography scans. As with other established imaging technologies, it has unique benefits as well as certain disadvantages, which include a limited field of view and vulnerability to imaging artifacts. However, software and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 133 publications
(165 reference statements)
0
22
0
4
Order By: Relevance
“…Different segmentation artefacts may also lead to incorrect OCTA results. However, software and hardware improvements are continually evolving to mitigate these limitations [31]. In addition, Enders, et al demonstrated that 91% of OCTA assessments exhibit acceptable quality for clinical interpretation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Different segmentation artefacts may also lead to incorrect OCTA results. However, software and hardware improvements are continually evolving to mitigate these limitations [31]. In addition, Enders, et al demonstrated that 91% of OCTA assessments exhibit acceptable quality for clinical interpretation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is an interferometric imaging technique that allows real‐time, high‐resolution and noninvasive imaging of biological tissue. [1] By overcoming the limitation of traditional ophthalmological imaging of retinal tomographic structures and functional imaging, it has become a popular standard tool for the evaluation and diagnosis of retinal diseases, such as diabetic macular edema (DME) [2], age‐related macular degeneration (AMD) [3] and glaucoma manifested through changes in the layer structure of the retina [4].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 10 , 11 FA and ICGA imaging are not used for treatment follow-up, because it is a time-consuming and invasive procedure that may cause serious adverse reactions. 12 Retreatment decisions are mostly based on OCT characteristics, such as intraretinal fluid or subretinal fluid (SRF) and increased retinal thickness. However, the vascular flow component of neovascularization activity is not visible on structural OCT. 10 …”
Section: Introductionmentioning
confidence: 99%
“…OCT angiography (OCT-A), an extension of OCT, visualizes the vasculature of the posterior pole in great detail without the need for intravenous administration of contrast agents. 12 14 Besides the en face assessment of the vascular network, this modality enables the depth-resolved assessment of abnormal retinal flow on cross-sectional B-scans. OCT-A may be a valuable additional imaging modality for neovascularization type classification by in-depth localization of abnormal flow, and it could also provide the currently missing information on the vascular flow component of neovascularization activity during treatment follow-up, enabling the optimization of retreatment strategies.…”
Section: Introductionmentioning
confidence: 99%